(untitled) (International Journal of Physiology, 2020)
Background: Epidemiological studies support a bidirectional relationship between serum testosterone and obesity as well as between testosterone and the metabolic syndrome. Low serum total testosterone predicts the development of central obesity and accumulation of intra-abdominal fat. Also low total and free testosterone and sex hormone binding globulin (SHBG) levels are associated with an increased risk of developing the metabolic syndrome, independent of age and obesity. Method: A cross sectional study was conducted on 100 male medical students (age 18 to 24 yrs). Blood samples were collected and investigated for serum testosterone level. Anthropometric measurements-BMI, Waist circumference and waist to hip ratio (WHR) were done. Results: 57 subjects out of 100 subjects with BMI <25 and serum testosterone level near to higher end of normal range and 43 subjects with BMI >25 and serum testosterone level near to lower end of normal range. 26 subjects with WHR <90 and serum testosterone level near to higher end of normal range and 74subjects with WHR >90 and serum testosterone level near to lower end of normal range. Conclusion: Serumtestosterone level increase with decrease in BMI and WHR. serumtestosterone level decrease with increase in BMI and WHR.Hence Sex hormone (Androgen) level is inversely related with obesity